Excitability in somatosensory cortex correlates with motoric impairment in amyotrophic lateral sclerosis. Issue 3 (3rd April 2019) - Höffken, Oliver; Schmelz, Alena; Lenz, Melanie; Gruhn, Kai; Grehl, Torsten; Tegenthoff, Martin; Sczesny-Kaiser, Matthias
Abstract: Objective: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative motoneuron disease. As previous studies reported alterations in motor cortex excitability, we evaluate excitability changes in somatosensory system. Methods: We examined 15 ALS patients and 15 healthy controls. Cortical excitability was assessed using paired somatosensory evoked potentials of median nerves. To determine disease severity and functional impairment, we assessed muscle strength and revised ALS-Functional Rating Scale (ALSFRS-R). Results: We found significantly reduced bilateral paired-stimulation inhibition in the ALS-group (both p  < 0.05). Additionally, paired-stimulation ratios significantly correlated with ALSFRS-R (left somatosensory cortex: r = −orte; right somatosensory cortex: r = −ort4; both p  < 0.05) and contralateral muscle strength (left somatosensory cortex: r = −orte, p  = 0.007; right somatosensory cortex: r = −ortex p  = 0.003). Conclusions: The results indicate disinhibition of the somatosensory cortex in ALS. It remains open if central somatosensory disinhibition is a primary characteristic of ALS as one element of a multisystem neurodegenerative disorder or a compensatory up-regulation due to functional motoric impairment. Longitudinal studies are necessary to categorize these findings.